(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article, as a result of a study of digitalization processes intensively carried out in countries around the world recently, widely covers issues related to the transfer of all industries of the Republic of Uzbekistan to a fast digital system. State laws and documents developed for the further development of the IT sector in the country have been disclosed. It also explains in detail the measures being implemented in Uzbekistan.